2015
DOI: 10.1007/s00497-015-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of BoMF25, a novel polygalacturonase gene involved in pollen development of Brassica oleracea

Abstract: BoMF25 acts on pollen wall. Polygalacturonase (PG) is a pectin-digesting enzyme involved in numerous plant developmental processes and is described to be of critical importance for pollen wall development. In the present study, a PG gene, BoMF25, was isolated from Brassica oleracea. BoMF25 is the homologous gene of At4g35670, a PG gene in Arabidopsis thaliana with a high expression level at the tricellular pollen stage. Collinear analysis revealed that the orthologous gene of BoMF25 in Brassica campestris (syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Moreover, the BoPG Bol018697 that belonged to clade F was dominantly expressed in Bud 5 in our result. This BoPG has been demonstrated to be closely related to pollen development by in situ hybridization and promoter expression analysis [ 14 ]. The possible functions of other BoPGs, especially the genes with higher expression levels, need further study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the BoPG Bol018697 that belonged to clade F was dominantly expressed in Bud 5 in our result. This BoPG has been demonstrated to be closely related to pollen development by in situ hybridization and promoter expression analysis [ 14 ]. The possible functions of other BoPGs, especially the genes with higher expression levels, need further study.…”
Section: Discussionmentioning
confidence: 99%
“…In Brassica rapa , the PGs BcMF2, BcMF6, BcMF16, BcMF17, and BcMF24 have been shown to play important roles in pollen development and pollen tube growth [ 9 , 10 , 11 , 12 , 13 ]. The PG gene BoMF25 in Brassica oleracea was proven to be related to the development of the pollen wall [ 14 ]. Recently, He et al [ 15 ] characterized the maize PG gene ZmPGH1 and demonstrated that it functions as a suppressor of programmed cell death in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Genes related to cell wall loosening were prominently expressed in DAH3615 and included in cluster 7 such as polygalacturonase (PG), expansins, pectate lyase, cellulase (glycosyl hydrolase family 5), endoglucanase, and glucan endo-1 3-beta-glucosidase 5. PG is involved in anther dehiscence [ 60 , 61 ], pollen mother cell wall degradation [ 62 ], pollen intine and exine formation [ 63 ], and pollen tube growth [ 64 ], while pectate lyase in pollen wall development [ 65 , 66 ] and pollen tube growth [ 67 , 68 ]. In this study, male-sterile flowers did not produce any pollen, since many genes related to pollen formation, development, and pollen tube growth were distinguishably expressed in the floral buds and flowers of DAH3615, but not in those of DAH3615-MS.…”
Section: Discussionmentioning
confidence: 99%
“…The ideal probe concentration will obtain good signal. In general, the probe concentration is controlled between 100 and 600 ng/ml in ISH [20, 21]. Some researchers suggested that the optimal probe concentration is related to the probe length and should be kept at 0.5 ng/µl/kb [22].…”
Section: Discussionmentioning
confidence: 99%